Independent and joint associations of glucose modified by high-density lipoprotein cholesterol with mortality in heart failure patients: evidence from the Jiangxi, China cohort - Jian, Guoan; He, Shiming; Jiang, Kun; Wang, Zhenyu; Wang, Juan; Lan, Houhui; Xie, Guobo; Sheng, Guotai; Fang, Yan; Wang, Wei; Zou, Yang (Frontiers in Endocrinology, 2025)
IntroductionMetabolic disorders characterized by dysregulation of glucose and lipid homeostasis are significant drivers of heart failure progression. This study proposes using high-density lipoprotein cholesterol (HDL-C) to modify fasting plasma glucose (FPG), and thereby constructing the FPG/HDL-C ratio (FHR) as a novel comprehensive metabolic indicator, and further investigates the synergistic effects of the FHR and its components on mortality in patients with acute decompensated heart failure (ADHF).MethodsThis cohort study included 2,328 ADHF patients recruited from the Jiangxi-ADHF II cohort. Multivariable Cox regression and restricted cubic spline models were used to analyze the association between the FHR and 30-day mortality in ADHF patients. To visualize the joint effects of FPG and HDL-C on 30-day mortality risk, we generated two-dimensional heatmaps and three-dimensional surface plots. Finally, mediation models were employed to perform exploratory analysis of the potential mediating roles of inflammatory factor white blood cells, oxidative stress marker gamma-glutamyl transferase, and nutritional factor albumin in the association between FHR and mortality risk.ResultsDuring the 30-day follow-up, 150 deaths (6.44%) occurred in the Jiangxi-ADHF II cohort. Multivariable Cox regression analysis revealed a positive association between FHR and 30-day mortality. Restricted cubic spline analysis showed a U-shaped association instead of a linear pattern, with the lowest mortality risk at FHR values ranging from 4 to 6. Notably, the joint association analysis based on two-dimensional heatmaps and three-dimensional surface plots, demonstrated a concave-shaped association of FPG and HDL-C with 30-day mortality: when both FPG (3–7 mmol/L) and HDL-C (1.05–1.65 mmol/L) were maintained within specific ranges, short-term mortality risk was minimized. Finally, mediation analysis suggested that inflammatory factor white blood cells and the nutritional factor albumin play significant mediating roles in the short-term mortality risk of ADHF patients associated with FHR.DiscussionThis cohort study of the Jiangxi population in China is the first to reveal a U-shaped association between FHR and 30-day mortality in ADHF patients, establishing a synergistic effect of FPG and HDL-C on mortality risk. Based on these findings, we propose implementing a “metabolic synergistic management” strategy for ADHF patients in clinical practice.